2015
DOI: 10.1080/1059924x.2015.1075451
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Accidents with Agricultural Machinery in Austria

Abstract: The number of recognized accidents with fatalities during agricultural and forestry work, despite better technology and coordinated prevention and trainings, is still very high in Austria. The accident scenarios in which people are injured are very different on farms. The common causes of accidents in agriculture and forestry are the loss of control of machine, means of transport or handling equipment, hand-held tool, and object or animal, followed by slipping, stumbling and falling, breakage, bursting, splitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Khurram 2015 [30] has reported that the most common pre-disposing factors for injuries were lapses in concentration while operating machinery, such as loss of synchronization between the person moving the roller and feeding the crop. Kogler 2016 [36] reports that the loss of machine control was a main cause of accident. According to Pickett 2001 [37], three quarters of the injuries reported were found to be either due to carelessness or else no specific reason was identified.…”
Section: Causes Of Injurymentioning
confidence: 99%
“…Khurram 2015 [30] has reported that the most common pre-disposing factors for injuries were lapses in concentration while operating machinery, such as loss of synchronization between the person moving the roller and feeding the crop. Kogler 2016 [36] reports that the loss of machine control was a main cause of accident. According to Pickett 2001 [37], three quarters of the injuries reported were found to be either due to carelessness or else no specific reason was identified.…”
Section: Causes Of Injurymentioning
confidence: 99%
“…This type of working equipment is very diffused and widely used in most agricultural activities, due to its multifunctional characteristics, ranging from use as a means of transportation in rural areas to its use for hauling a trailer or other working equipment (e.g., an atomizer, a plough, etc. ), or as a static power unit (e.g., for running a pump or a saw bench through the tractor's power take-off (PTO)) [23][24][25][26][27][28][29]. Such multi-functionality has determined the tractor's classification as a vehicle and working equipment at the same time, meaning that from a safety point of view, an interwoven set of legislative requirements applies, contributing to the difficulties of both producers and users in guaranteeing an adequate safety level [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16]. Also the involvement of both users and equipment providers of agriculture machinery is important to properly analyse risk factors and the effectiveness on preventive and protective measures adopted, since it is recognized that most of occupational accidents are caused by unsafe conditions and unsafe behaviours [14,[17][18][19][20][21]. Therefore, performing risk assessment in a sequential manner (i.e.…”
Section: Introductionmentioning
confidence: 99%